2020
DOI: 10.1002/pen.25502
|View full text |Cite
|
Sign up to set email alerts
|

The effect of thermal treatment on the properties of expanded polystyrene

Abstract: Expanded polystyrene (EPS) is a commonly used polymer in the packaging industry and for the thermal insulation of buildings. It has poor mechanical properties, which limit its application in some areas. A heat treatment was carried out on a sample of EPS, in order to improve its mechanical properties. The treatment consists of operations that combine the heating and cooling of the material. It is executed to improve the characteristics of the treated polymer and make it more favorable for use in new applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…It has been shown that the water bath heat treatment of cured microspheres can effectively eliminate residual internal stresses and reduce the cracking rate of microspheres. [ 31,33 ] The TGA results of the polymer showed that some FB remained in the PS microspheres, thus the PS glass transition temperature was reduced. The glass transition temperature of the PS microspheres is 103°C.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the water bath heat treatment of cured microspheres can effectively eliminate residual internal stresses and reduce the cracking rate of microspheres. [ 31,33 ] The TGA results of the polymer showed that some FB remained in the PS microspheres, thus the PS glass transition temperature was reduced. The glass transition temperature of the PS microspheres is 103°C.…”
Section: Resultsmentioning
confidence: 99%
“…industry (Khoubi‐Arani, 2024; Pech‐Mendoza et al, 2024; Solomon & Hemalatha, 2020). However, its wide application is still restricted due to its extremely poor mechanical properties, flammable nature, low UV resistance, and glass transition temperature (Ellouze et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Zouzias [23] performed lengthy experiments to characterize the tensile behavior of EPS foams of densities ranging from 60-120 kg/m 3 and verified that the tensile strength also rises with the increase of strain rates and density. Apart from fundamental mechanical properties investigation, Ellouze [24] carried out a heat treatment process on EPS foams and enhanced the hardness. Nevertheless, the mechanical properties test for the treated and non-treated EPS foam followed different standards, which could impair the comparability of experimental results.…”
Section: Introductionmentioning
confidence: 99%